2013
DOI: 10.1088/0953-8984/25/7/075503
|View full text |Cite
|
Sign up to set email alerts
|

Wavefunctions, quantum diffusion, and scaling exponents in golden-mean quasiperiodic tilings

Abstract: We study the properties of wavefunctions and the wavepacket dynamics in quasiperiodic tight-binding models in one, two, and three dimensions. The atoms in the one-dimensional quasiperiodic chains are coupled by weak and strong bonds aligned according to the Fibonacci sequence. The associated d-dimensional quasiperiodic tilings are constructed from the direct product of d such chains, which yields either the hypercubic tiling or the labyrinth tiling. This approach allows us to consider fairly large systems nume… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…It is well known that the spectrum of the Fibonacci Hamiltonian is fractal [37], as illustrated in the top panel of fig. (2) which shows the integrated density of states, idos(E) defined by the fraction of states of energy smaller than E. The fractal dimensions of the spectrum can be computed in the limits ρ ∼ 1 [31] and ρ 1 [27]. The structure of the eigenstates is also well understood in these two limits [19,21,32,39]. Away from these limits, however, the structure of the eigenstates is not known, with the notable exception of the E = 0 state at the center of the spectrum shown in fig.…”
Section: A the Fibonacci Chain And Hopping Hamiltonianmentioning
confidence: 99%
“…It is well known that the spectrum of the Fibonacci Hamiltonian is fractal [37], as illustrated in the top panel of fig. (2) which shows the integrated density of states, idos(E) defined by the fraction of states of energy smaller than E. The fractal dimensions of the spectrum can be computed in the limits ρ ∼ 1 [31] and ρ 1 [27]. The structure of the eigenstates is also well understood in these two limits [19,21,32,39]. Away from these limits, however, the structure of the eigenstates is not known, with the notable exception of the E = 0 state at the center of the spectrum shown in fig.…”
Section: A the Fibonacci Chain And Hopping Hamiltonianmentioning
confidence: 99%
“…Thus the wavefunctions are not multifractal at this order in ρ and multifractality appears only at the nextto-leading order, as discussed in the next section. This first-order description of the wavefunctions has been compared to numerical results in [20], where the agreement was found not to be very good. We argue that this is because the wavefunctions becomes rapidly multifractal as ρ is increased.…”
Section: B Fractal Dimensions Of the Wavefunctionsmentioning
confidence: 99%
“…By keeping in mind the main results reviewed in this work concerning the spatial structure of the wave functions belonging to fractal and QPS, it could be concluded that the recent trend of abandoning the former use of "critical wave function" to generically refer to all eigenstates belonging to singular continuous spectra should be encouraged [92]. In fact, whereas the electronic states found in the Aubry-André self-dual model can be properly regarded as being strictly critical ones (in the sense that they undergo a metal-insulator critical transition) this criterion no longer holds for the states found in both fractal and QPS, albeit all of them display multifractal properties.…”
Section: Outlook and Perspectivesmentioning
confidence: 99%